Tendencies in User Interface Development (Modelling) for DSS Needs - Bojar, Waldemar (Advanced Information Technologies for Management – AITM 2009, 2009)
In the paper some principles and trends in User Interface (UI) design were shown. Especially selected functional and exploitation characteristics of well designed UI in context of Decision Support Systems user needs were highlighted. Review of appropriate literature allows to conclude that evolutionary approach and interactive process of UI updating should be preferred but some standardized exploitation principles in application design have to be saved to avoid errors and too extended costs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 9-19